Time-resolved observation of structural change of copper induced by laser shock using synchrotron radiation with dispersive XAFS. Issue 3 (2nd July 2016) - Niwa, Yasuhiro; Sato, Tokushi; Ichiyanagi, Kohei; Takahashi, Kei; Kimura, Masao
ABSTRACT: We report a single-shot nanosecond time-resolved dispersive XAFS measurement of copper foil under laser-induced shock compression. Obtained EXAFS results indicated clearly the structural evolution, though XANES spectra showed that the laser irradiation does not affect the copper electronic state. The nearest (ca. 0.22 nm) and longer (ca. 0.44 nm) Cu–Cu distances are changed at 4 and 200 ns, respectively, in the radial structure functions (RSFs). It was revealed that an average compression of 2% occurs at 4 ns and is released within 200 ns. It was found that the fragmentation of the copper begins at around 200 ns according to the increase in distance of the RSF.